Seaweed supply chain risk assessment in Sabah - Mahmud @ Mansor, Mohd; Kamarulzaman, Nitty Hirawaty (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Seaweed-based industry, as in any other agricultural-based activity are not shy of risks and uncertainties that are ubiquitous and varied within itself, and it is including vagaries of weather, the unpredictable nature of biological processes, the pronounced seasonality of production and market cycles, and the geographical separation of production. Given the vast industry potential, it is imperative to manage and mitigate any potential risks in its supply chain (SC) which may cause disruption and give adverse impacts to the whole industry. By applying the concept of SC risk management, the objectives of this study are to identify and assess various risks along the seaweed SC in Sabah. Data were collected using face-to-face, in-depth interview with Key Informants (KIs) (n = 22) to discover as much as possible risk source along the SC. Interviews were transcribed and analysed using thematic analysis with ATLAS.ti. The analysed data then were processed using Fuzzy FMEA (Failure Mode and Effect Analysis) to assess those risks. The result has shown that there are 18 main sources of risks in the SC which were further divided into six types. The highest would be “inconsistent material quality” with the Fuzzy Integral value of 7.729 out of 10 dues to its potential cascading effect along the SC. As a conclusion, this research has successfully identified, categorised and assessed 42 risk factors that have the probability to disrupt the supply chain. Should stakeholders or policymakers like to ensure the sustainability of the industry, those are risks that should be paid more attention to increase the resilience of the SC.